Saemaul Undong: Responsible leadership for just development in South Korea - Yoon, I Sil 19XX- (HTS teologiese studies, 2024)
Saemaul Undong, also called the New Village or Community Movement, was a community-based development programme promoted in the Republic of Korea during President Park’s regime in the 1970s. To reduce the urban-rural income gap in a relatively short period of time (the decade of the 1970s), it has brought unprecedented success, as seen in South Korea’s overall socioeconomic improvements and decrease of extreme poverty. Based on the movement’s contributions, individual research and public discourse have argued for the potential of applying Saemaul Undong’s strategies and activities to developing countries. Nevertheless, the movement’s weaknesses, such as the government’s ignorance of the particular needs of rural populations and the sustenance of dictatorship, imply the necessity for fundamental changes in the goals and policies of Saemaul Undong before it can be utilised for different contexts. This article explores how the limitations of Saemaul Undong should be amended.Contribution: This article utilises Emmanuel Levinas’ ‘Ethics of the Other’ as an effective framework that can be used to critique, in particular, the top-down and ambitious approach of the movement and address the significance of responsible leadership that, with hospitality, promotes a just society by being attentive to the suffering of socially vulnerable populations, concerning their dignity, uniqueness, and equality.